Overweight/Obesity among adult (20 years old and over) residents of urban Barangays anchoring the Iloilo River. - Cueva, Lorelei; Grino, Lowela May.
This study aimed to determine the prevalence of overweight/obesity among adult (20 years old and over) residents of urban barangays anchoring the Iloilo River.
Research Paper (Undergraduate, Bachelor of Science in Public Health) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo
Keywords: Adults -- Obese